Performance of herbicides on effective weed management in soybean (Glycine max) crop - SINGH, R K; TRIPATHI, UTTAM KUMAR; SINGH, S R K (The Indian Journal of Agricultural Sciences, 2020)
Field experiment was conducted to study the efficacy of different post-emergence herbicides in the soybean (Glycine max (L.) Merr.). The selected herbicides were applied individually or in combination in soybean. A series of experiments were conducted during 2013 to 2017. Application of quizalofop-p-ethyl + chlorimuron ethyl and fenoxaprop-p-ethyl + chlorimuron ethyl along with surfactant at 15 days after sowing (DAS) were found effective herbicides for control of broad leaf weed and grasses in soybean crop. It was observed that post-emergence application of quizolofop-p-ethyl (50 g a.i.) + chlorimuron ethyl (6 g a.i./ha) significantly reduce the weed population (8/m2), weed dry matter (2.3), weed index (0) and highest weed control efficiency (92.9%) and grain yield (1.77 t/ha) at 45 DAS followed by fenoxaprop-p-ethyl (50 g a.i.) + chlorimuron ethyl (6 g a.i./ha) compared to other treatments. Application of quizolofop-p-ethyl (50 g a.i.) + chlorimuron ethyl (6 g a.i./ha) was found to minimize the loss (44.06%) caused by weeds and there by improve the uptake of water, air, and nutrition by the crop plants. Further, application of quizalofopp- ethyl + chlorimuron ethyl + surfactant enhanced the number of nodule/plant (52.00), nodule diameter (5.00 mm) and nodule weight (187.2 mg/plant) followed by fenoxaprop-p-ethyl + chlorimuron ethyl + surfactant as compared to other treatments. Highest yield was recorded in the plants treated with quizalofop-p-ethyl + chlorimuron ethyl + surfactant in combination compared to other treatments. Quizalofop-p-ethyl and fenoxaprop-p-ethyl + chlorimuron ethyl along with surfactant were found to highly comparable in terms of price and yield compared to other methods of weed control including hand weeding. This combination can be recommended for the control of both broad and narrow leaf weed the soybean crop.